Organophosphorus Insecticide Poisoning Related Mortality and Neurotoxicity in Sabzevar - Soroosh, Davood; Ranjbar, Narges; Nematshahi, Mohammad; Javadinia, Seyed Alireza (International Journal of Medical Toxicology and Forensic Medicine, 2020)
Background: This study aimed to assess mortality and neurotoxicity caused by the pesticide organophosphate and its correlation with the type of poison and treatment in patients admitted to Vasei Hospital of Sabzevar City, Iran, in 2018. Methods: Out of 122 cases, 52 patients (43.3%) were male, and 70 patients (56.9%) were female. The Mean±SD age of the men was 32.65±29.15, and women was 30±15.30 years. Results: Mortality in women and men was 10% and 17.3%, respectively. Among treated people, diazinon had the highest frequency of 76.4%, and among dead people from diazinon and malathion had the highest rates of 56.3% and 43.8%, respectively. Conclusion: The prevalence of mortality in patients was 7.3% (n=9). As most people with organophosphorus poisoning have been exposed to diazinon toxins; therefore, strategies to prevent and reduce exposure to this toxin are essential.